2021
DOI: 10.1063/5.0062823
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal multiscale porous adhesive (bio)inks facilitate scaffold integration

Abstract: Poor cellular spreading, proliferation, and infiltration, due to the dense biomaterial networks, have limited the success of most thick hydrogel-based scaffolds for tissue regeneration. Here, inspired by whipped cream production widely used in pastries, hydrogel-based foam bioinks are developed for bioprinting of scaffolds. Upon cross-linking, a multiscale and interconnected porous structure, with pores ranging from few to several hundreds of micrometers, is formed within the printed constructs. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 76 publications
2
28
0
Order By: Relevance
“…Further, motor neuron progenitor genes including HB9, ISLET1, and MAP2 were noticeably increasing, while GFAP was decreasing in the porous group, indicating that the majority of NSCs were converted into relatively mature neurons/motoneurons. Previous research has shown that different cell types may require different microporous sizes within hydrogel for maximum tissue growth, with the optimal average pore size ranging from a few to hundreds of micrometers . In the present study, with an average diameter of 168 ± 71 μm and suitable modulus, the migration and differentiation rates of NSCs were enhanced.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Further, motor neuron progenitor genes including HB9, ISLET1, and MAP2 were noticeably increasing, while GFAP was decreasing in the porous group, indicating that the majority of NSCs were converted into relatively mature neurons/motoneurons. Previous research has shown that different cell types may require different microporous sizes within hydrogel for maximum tissue growth, with the optimal average pore size ranging from a few to hundreds of micrometers . In the present study, with an average diameter of 168 ± 71 μm and suitable modulus, the migration and differentiation rates of NSCs were enhanced.…”
Section: Resultssupporting
confidence: 90%
“…Previous research has shown that different cell types may require different microporous sizes within hydrogel for maximum tissue growth, with the optimal average pore size ranging from a few to hundreds of micrometers. 31 In the present study, with an average diameter of 168 ± 71 μm and suitable modulus, the migration and differentiation rates of NSCs were enhanced.…”
Section: Porous Hydrogel Enhancedsupporting
confidence: 46%
“…At each time point (1, 2, 3, and 4 days), the samples were removed from the solution and weighed ( W 2 ) to determine the mass changes after degradation. The normalized mass (%) 43 was calculated using Equation (2): Normalized mass0.25em()%=W20.25emW1×100 …”
Section: Methodsmentioning
confidence: 99%
“…[66,67] Previous reports have shown that the presence of microarchitecture, such as pores, may increase the water holding capacity of scaffolds. [68][69][70] We assessed whether hollow channels generated by chaotic printing may play a similar role by evaluating the swelling ratio of filaments printed using 3 and 5 KSM elements within the printhead. In this experiment, the permanent and fugitive inks were high-viscosity alginate and pluronic, respectively.…”
Section: Water Holding Capacity In Filaments With Inner Hollow Channelsmentioning
confidence: 99%